Lay health coaching intervention for older adults with chronic diseases: study protocol for a pragmatic randomised controlled trial - Edwin K. H. Chung; Eliza Lai-Yi Wong; Hera Hiu-Wah Leung; Dannii Y. Yeung; Eng-Kiong Yeoh; Frank Youhua Chen (Trials)
Abstract Background A large proportion of older adults suffer from chronic diseases. Health coaching is a promising intervention that enhances individuals’ health knowledge and supports changes in health behaviours. Even though health professionals usually conduct health coaching interventions, lay health workers from different backgrounds account for a growing segment of health coaches over the years. The planned study’s main objective is to investigate whether health coaching by lay health workers is as effective as that by health professionals. Methods The effects of health coaching intervention by lay health workers will be examined in comparison with that by health professionals within a single-blind, multi-centre, randomised controlled trial with a follow-up assessment after 3 months. A total of 380 community-dwelling older adults with chronic diseases will be recruited and randomly assigned using a 1:1 ratio into the intervention and control groups. The intervention group will receive a 3-month health coaching intervention delivered by lay health workers, whereas the control group will receive the intervention delivered by health professionals. Primary outcomes include patient activation, physical activity and nutrition behaviours. Discussion The expected findings of this study will advance the health coaching literature, research and practice by determining whether health coaching by lay health workers is as effective as that by health professionals in enhancing older adults’ knowledge, skills and confidence in chronic disease self-management and promoting changes in health behaviours. If proven effective, the inclusion of lay health workers in delivering effective self-management interventions should be advocated to reduce the over-reliance on health professionals in the primary healthcare system. Trial registration ISRCTN, ISRCTN73836238 . Registered 8 November 2023.